The oldest scene of the Entrance of the Virgin Mary into the Temple? A new identification of wall paintings from the Faras Cathedral - Magdalena Łaptaś (Polish Archaeology in the Mediterranean)
This paper offers a new identification of two paintings executed on the first layer of plaster in the northern transversal aisle of the Faras Cathedral, which, due to their poor state of preservation at the time of discovery, were impossible to remove from the walls. Interpretations to date have linked the first painting with the Apostles or Christ teaching in the Temple and the second one with the Resurrection cycle or treated both scenes as unidentified. I propose, instead, that both paintings belonged to the cycle of the Childhood of the Virgin and showed her entrance to the Temple and being fed by an angel. This identification, based on a comparison of these scenes with Cappadocian and Byzantine masterpieces, is further reinforced by the placement of the paintings within the iconographic program of the Faras Cathedral.